The Crescent Lake copper deposit, central Newfoundland: deep levels of a volcanogenic hydrothermal system? - Waldie, Craig; Jowett, E.; Swinden, H. (Atlantic Geology, 1991)
The Crescent Lake Mine, near the village of Robert's Arm in central Newfoundland, produced small tonnages of high-grade copper ore from quartz veins in the late 1800's and the 1920's. Although a Crescent Lake-type deposit is not a viable exploration target in itself, its presence has been used to suggest a potential for either volcanogenic massive sulphides (VMS) such as the nearby Pilley's Island deposit, or for mesothermal or epithermal gold. Field relationships, petrography, geochemistry, mineral chemistry, and fluid inclusion and stable isotopic studies are used to constrain the genesis of the deposit Mineralization occurs in four sulphide stages and a late oxide stage, distinguished by ore microscopy. Sphalerite, galena, chalcopyrite, and newly recognized carrollite were deposited with quartz between two pyrite stages. Covellite and iron oxides indicate later oxidation. Fluid inclusions in vein quartz are aqueous fluid-vapour type with no daughter crystals, no C02 or CH4, no boiling, and a narrow range of salinities (~ 3-7% NaCl ^). The sulphides were likely deposited from homogeneous fluids at >430 m depth. The wide range of homogenization temperatures (~112-250°C) can be interpreted as the result of either changing temperature or fluctuating fluid pressures during the episodic crack-seal vein formation. Ore-related chlorite has a distinctive blue birefringence and higher Fe/Fe+Mg values (- 0.51 vs. 0.42) than chlorite in barren host rock, similar to other VMS deposits. The average calculated crystallization temperature of hydrothermal chlorite (240 ± 2°C) is close to the maximum fluid inclusion homogenization temperatures and likely closer to the true fluid trapping temperature. Sulphur isotope determinations (IP'S » S.4; d^S = 2.8; duSt » 2.2) are similar to the Gull Pond VMS deposit; they indicate isotopic disequilibrium between coeval sulphides but a homogeneous sulphur source during the ore-forming event. This study concludes that the Crescent Lake copper deposit is most likely part of a volcanogenic hydrothermal stockwork, possibly genetically related to the Pilley's Island deposit.